2021
DOI: 10.3390/cancers13040916
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of the p53 Family and Gastric Cancer: A Ménage à Trois for an Unfinished Affair

Abstract: Gastric cancer is one of the most aggressive cancers, with a median survival of 12 months. This illustrates its complexity and the lack of therapeutic options, such as personalized therapy, because predictive markers do not exist. Thus, gastric cancer remains mostly treated with cytotoxic chemotherapies. In addition, less than 20% of patients respond to immunotherapy. TP53 mutations are particularly frequent in gastric cancer (±50% and up to 70% in metastatic) and are considered an early event in the tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 378 publications
0
19
0
Order By: Relevance
“…In addition, it has been demonstrated that over 50% of human tumors are characterized by mutations of p53, leading to the enhanced survivability of tumor cells [ 37 , 38 , 39 ]. The role of p53 is particularly important in gastric cancer, where the inactivation of p53 correlates with the response to chemotherapy [ 40 ]. Western blot was used to measure the p53 protein levels [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been demonstrated that over 50% of human tumors are characterized by mutations of p53, leading to the enhanced survivability of tumor cells [ 37 , 38 , 39 ]. The role of p53 is particularly important in gastric cancer, where the inactivation of p53 correlates with the response to chemotherapy [ 40 ]. Western blot was used to measure the p53 protein levels [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the absence of a wild type p53 function results in resistance to anticancer agents, such as cisplatin. In gastric cancers, overexpression of p53 is strongly linked to its mutational status, also correlating to resistance to cisplatin [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In our PDX model, diffuse and homogenous p53 nuclear staining was observed in controls, related to the p53 mutation (exon8:c.844C > T:p.R282W).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the survival rate of patients' ongoing palliative therapies remains very low, as the majority (75%) of tumors are chemoresistant at late stages. The exact molecular basis of the resistance is not yet fully understood, despite the identification of several mechanisms, i.e., tissue-independent, such as the mutation in p53, the overexpression of DNA repair effector ERCC1 and the expression of ABC transporters, or tissue-specific [7,8]. In addition to altered/mutated intracellular mechanisms within the cancer cells, the tumoral microenvironment also plays an important role in the resistance to treatment by impacting the cancer cell survival via metabolites, mechanical stresses, and non-cancerous cells, such as cancer associated fibroblasts [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the identity of the key oncogene or tumor suppressor gene that drives the initial transformation process and/or maintains the transformed status (named “driver mutation”) varies between organs and even between the different tissues within a given organ. For instance, admittedly, inactivating mutations or alterations of p53 can be seen as a key primary event for the transformation of epithelial gastric cells, but it is not the same for glioblastoma or colon cancer, in which different tumor suppressor genes are primarily mutated (e.g., APC for colon cancer) [ 2 ]. In addition, the mutation or alteration affecting an individual gene may also differ between cancers.…”
Section: Introductionmentioning
confidence: 99%